2012
DOI: 10.1590/s0103-84782012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência térmica de telhas onduladas de fibrocimento aplicadas em abrigos individuais para bezerros expostos ao sol e à sombra

Abstract: Eficiência térmica de telhas onduladas de fibrocimento aplicadas em abrigos individuais para bezerros expostos ao sol e à sombra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
1
7
0
3
Order By: Relevance
“…It was verified that the inner surface temperature (IST) of both roofs followed the same pattern (Table 2), with the lowest values in the early hours of the day, reaching the maximum value between 12h and 14h (period with maximum solar radiation), and then decreasing at the end of the day. Similar behavior was observed by Fiorelli et al (2012), who have found the higher temperature at 14h. Almeida and Passini (2013), studied different types of roofing and also checked an increase in the air temperature, reaching the peak at 14h and decreasing thereafter.…”
Section: Resultssupporting
confidence: 88%
“…It was verified that the inner surface temperature (IST) of both roofs followed the same pattern (Table 2), with the lowest values in the early hours of the day, reaching the maximum value between 12h and 14h (period with maximum solar radiation), and then decreasing at the end of the day. Similar behavior was observed by Fiorelli et al (2012), who have found the higher temperature at 14h. Almeida and Passini (2013), studied different types of roofing and also checked an increase in the air temperature, reaching the peak at 14h and decreasing thereafter.…”
Section: Resultssupporting
confidence: 88%
“…A necessidade de projetar instalações adaptadas, com características construtivas diferenciadas que garantam o conforto e permitam, ao animal, melhor desempenho produtivo (Fiorelli et al, 2012). Desta forma, as coberturas verdes, além de contribuir para a redução dos índices de conforto apresentam outras vantagens, como a redução do escoamento superficial (Stovin et al, 2012), da poluição do ar (Gartland, 2010), dos ruídos (Renterghem & Botteldooren, 2009) e da transmissão de energia para o interior da construção.…”
Section: Resultsunclassified
“…Furthermore, these buildings are planned to be economically viable and healthy places to live and work (GHAFFARIANHOSEINI et al, 2013). This concept can also be applied to rural buildings where environmental comfort requirements are essential to ensure a higher animal welfare (FIORELLI et al, 2012) and, consequently, a greater quantity and quality of production of meat.…”
Section: Introductionmentioning
confidence: 99%